2011
DOI: 10.1016/j.aquatox.2011.06.021
|View full text |Cite
|
Sign up to set email alerts
|

Long-term food-exposure of zebrafish to PCB mixtures mimicking some environmental situations induces ovary pathology and impairs reproduction ability

Abstract: Although the use of polychlorinated biphenyls (PCBs) has been banned for several decades, they are still present in the environment and are occasionally mechanically released from sediment or transferred through the trophic chain. Field analyses have established correlations between exposure to PCBs and alterations in fish physiology including reproductive function. Experimental exposures have been mainly performed using dioxin-like PCBs or other congeners at very high concentrations. However, these studies ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
45
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 61 publications
8
45
1
Order By: Relevance
“…A variety of environmental contaminants such as hepatochlor (Miller et al, 1999), dieldrin (Richardson et al, 2006), certain PCBs, organochlorine pesticides, metals and bisphenol A (Jones and Miller, 2008) have been shown to influence dopamine homeostasis in mammals and the hypothalamic-pituitary-gonadal axis in fishes (Khan and Thomas, 2006;Martyniuk et al, 2010;Page et al, 2011). Long-term dietary exposure of zebrafish to PCB mixtures mimicking environmental situations resulted in a decrease of maturing follicles and a reduction of fertilization rate (Daouk et al, 2011). In zebrafish, exposure to pentachlorophenol and methoxychlor inhibited oocyte maturation (Tokumoto et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A variety of environmental contaminants such as hepatochlor (Miller et al, 1999), dieldrin (Richardson et al, 2006), certain PCBs, organochlorine pesticides, metals and bisphenol A (Jones and Miller, 2008) have been shown to influence dopamine homeostasis in mammals and the hypothalamic-pituitary-gonadal axis in fishes (Khan and Thomas, 2006;Martyniuk et al, 2010;Page et al, 2011). Long-term dietary exposure of zebrafish to PCB mixtures mimicking environmental situations resulted in a decrease of maturing follicles and a reduction of fertilization rate (Daouk et al, 2011). In zebrafish, exposure to pentachlorophenol and methoxychlor inhibited oocyte maturation (Tokumoto et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…5) Sharma et al (2017) investigated effects of lead nitrate on Channa striatus ovaries and they detected severe histopathological changes in oocyte and connective tissue structure. Daouk et al (2011) observed decrease in the number of mature oocytes and an increase in the number of atretic oocytes in zebrafish ovaries after long-term exposure to polychlorinated biphenyls mixtures. They also noticed slight decrease in number of follicles at stage III (vitellogenic) and stage IV (mature oocyte), in comparison with control.…”
mentioning
confidence: 93%
“…Polychlorinated biphenyls (PCBs) are lipophilic industrial chemicals that accumulate in living organisms (Okumura et al, 2003;Van Geest et al, 2011) and have negative physiological effects, mostly on the reproductive system of vertebrates, including fish (Khan and Thomas, 1997Gore et al, 2002;Coimbra et al, 2005;Gregoraszczuk et al, 2005;Coimbra and Reis-Henriques, 2007;Daouk et al, 2011). The impairment of reproduction in teleosts was found at a central level, at the hypothalamo-pituitary-gonadal axis, after the exposure to different PCB mixtures.…”
mentioning
confidence: 99%
“…In females (Atlantic croaker, Nile tilapia, and zebrafish (Danio rerio)) exposed to PCBs, the observations include decreased ovary growth, the absence of maturing oocytes, and an increased number of atretic follicles Coimbra and Reis-Henriques, 2007;Daouk et al, 2011).…”
mentioning
confidence: 99%
See 1 more Smart Citation